(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The cells and secondary metabolites from Lactic Acid Bacteria (LAB) provide a biological food preservative suitable as an alternative to the use of chemical in extending food shelf life. The present research was aimed at examining the potential of crude bacteriocin from LAB isolated from the gut of mouse as a bio-control measure against the commonly encountered food spoilage bacteria. Compared to lactic acid bacteria (LAB) from other sources, including fermented foods, LAB from the mouse gut show better persistence and gut microbiota regulation. Their special adaptations to the gastrointestinal environment of mice increase their efficacy as probiotics by strengthening the intestinal barrier and boosting immune responses. Using standard microbiological methods, LABs were isolated from the gut of a mouse on De Mann Rogosa Agar (MRSA), characterized and identified. Crude bacteriocin was obtained from broth culture of the isolates and tested for antibacterial activity against Pseudomonas aeruginosa, Escherichia coli, Bacillus megaterium. Bacillus cereus and Staphylococcus aureus using agar well diffusion method. Four species of LAB were obtained and identified, three of which were Lactobacillus species 1, 3, and4 while one was a Lactococcus species. Crude bacteriocin from the Lactococcus species was the most effective against all the tested bacteria except B. megaterium, crude bacteriocin from Lactobacillus species 1and 3 were not effective against E. coli and B. megaterium while the crude bacteriocin from Lactobacillus species 4 was active against only S. aureus. Staphylococcus aureus was the most sensitive to the crude bacteriocins with an average zone of growth inhibition of...